On The Economics of Forest Carbon: Renewable and Carbon Neutral But Not Emission Free - Jussi Lintunen; Jussi Uusivuori (Fondazione Eni Enrico Mattei (FEEM), 2014)
First-best optimal forest sector carbon policy is examined. Using a comprehensive forest sector model with a detailed carbon cycle section we show that the renewability and carbon neutrality arguments do not warrant emission free treatment of forest bioenergy. However, under the biomass stock change carbon accounting convention followed by UNFCCC and IPCC, the forest owners pay for the roundwood emissions and, to avoid double counting, the use of roundwood is treated as emission free. The bioenergy from harvest residues cannot be treated as emission free either. Their emission factors are determined through the decay time-scales specific to residue fractions and discount rate used in welfare assessment. In addition, we show that an optimal policy subsidizes the production of wood products sequestering carbon. The relative magnitude of the subsidy is based on the fraction of the carbon stored, the lifetime of the products and the discount rate. Correspondingly, the carbon removals by biomass growth are subsidized and the harvest residue generation taxed. Further, we show that the supply side policies are independent of final use of harvested timber. Numerical solution of the model shows that, although the use of wood is not emission free, it is optimal to increase the use of wood, possibly also in the energy sector. Before the wood use can be increased, the forest biomass has to be increased. This initial carbon sink speeds up the convergence to the lower steady-state atmospheric carbon stock.
Keywords: Q23; Q43; Q50; Q54; 330; Optimal Policy; Forest Carbon; Effective Emission Factor; Age-Structured Forest